Optimizing the Care Coordinator Role in Primary Care: A Qualitative Case Study. Issue 2 (April 2017) - Clark, Elizabeth C.; Howard, Jenna; Ferrante, Jeanne; Heath, Cathryn; Li, Kang; Albin, Susan; Hudson, Shawna V.
Abstract : Background: Care coordinators (CCs) are increasingly employed in primary care as a means to improve health care quality, but little research examines the process by which CCs are integrated into practices. This case study provides an in-depth examination of this process and efforts to optimize the role. Methods: Two CCs' work was observed and assessed, and attempts were made to optimize the role using workflow modeling and "Plan-Do-Study-Act" cycles. Rolling qualitative analyses of field notes from key informant interviews and team meetings were conducted using iterative cycles of "immersion/crystallization" to identify emerging themes. Results: Expected roles of CCs included case management of high-risk patients, transitions of care, and population management. Case management was the least difficult to implement; transition management required more effort; and population management met with individual and institutional obstacles and was difficult to address. Conclusions: The process by which CCs are integrated into primary care is not well understood and will require more attention to optimally use this role to improve health care quality. Understanding aspects of CCs' roles that are the least and most difficult to integrate may provide a starting place for developing best practices for implementation of this emerging role.